The study of drug interaction on pneumonia patients at RSUP Dr. M. Djamil Padang - Lola Azyenela; Mimi Aria; Lana Aristya (Universitas Islam Indonesia, 2022)
AbstractBackground: Pneumonia is one of the diseases that cause high rates of toddler deaths in the world. In Indonesia, pneumonia is the second cause of death of infants and toddlers after diarrheal diseases. Most pneumonia patients are treated with other diseases so many pneumonia patients receive more than two types of drugs in one prescription, this has the potential for drug interactions with drugs.Objective: The aim of this study was to look at potential occurrences of drug interactions in toddler patients at Dr.M. Djamil Padang Hospital hospitalized in 2019.Methods: This research was nonexperimental research design with cross-sectional descriptive methods of analysis and the data retrieved retrospectively. The patient's medical records were analyzed using the Drugs.com software and Medscape.Results: There were 62 patients who met the inclusion criteria. Among them, there were 5 pneumonia patients (8.1%) who experienced drug interactions with drugs, with the pharmacokinetic category as many as 3 cases (42.9%) affecting metabolism and drug interactions in the pharmacodynamic category by 4 cases (57.1%). Based on the severity of drug interactions, this study found 1 minor case (14.3%), 5 moderate cases (71.4%), and 1 major case (14.3%).Conclusion: From the results of the study it can be concluded that there was a potential for drug interactions in pneumonia toddler patients at Dr.M. Djamil Padang Hospital in the period 2019.Keywords: Bronchopneumonia, drug Interactions, toddlerIntisariLatar belakang: Pneumonia merupakan penyakit infeksi saluran pernapasan penyebab kematian utama pada balita di seluruh dunia. Di Indonesia, pneumonia menduduki peringkat kedua penyebab kematian bayi dan balita setelah diare. Pneumonia dapat disebabkan karena bakteri yang menyerang saluran pernapasan. Tatalaksana terapi pada pneumonia umumnya kombinasi beberapa obat. Hal ini berpotensi menimbulkan masalah pengobatan khususnya interaksi obat. Tujuan: Penelitian ini bertujuan untuk melihat kejadian interaksi obat pada pasien balita di instalasi rawat inap anak RSUP Dr. M. Djamil tahun 2019. Metode: Desain penelitian yang digunakan adalah cross-sectional deskriptif dengan pengambilan data secara retrospektif melalui rekam medis pasien. Setiap jenis obat yang tertulis rekam medis dianalisis dengan menggunakan bank data dari software Drug.com dan Medscape. Hasil: Data diambil dari 62 pasien, berdasarkan jumlah tersebut dapat diidentifikasi 5 pasien mengalami interaksi obat (8,1%), terdiri dari 71,4% moderat, 14,3% minor dan 14,3% mayor. Kesimpulan: Interaksi obat yang sering terjadi pada pasien balita dengan pneumonia adalah penggunaan kaptopril dengan furosemid. Kata kunci: Balita, interaksi obat, pneumonia